2003
DOI: 10.1080/1071576021000040664
|View full text |Cite
|
Sign up to set email alerts
|

Derivatives of Xanthic Acid are Novel Antioxidants: Application to Synaptosomes

Abstract: Xanthic acids have long been known to act as reducing agents. Recently, D609, a tricyclodecanol derivative of xanthic acid, has been reported to have anti-apoptotic and anti-inflammatory properties that are attributed to specific inhibition of phosphatidyl choline phospholipase C (PC-PLC). However, because oxidative stress is involved in both of these cellular responses, the possibility that xanthates may act as antioxidants was investigated in the current study. Finding that xanthates efficiently scavenge hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 54 publications
2
28
0
Order By: Relevance
“…GSH can also protect brain from damage by peroxynitrite, hydroxyl free radicals, or reactive alkenals [63][64][65][66]75]. D609 may binds to reactive alkenals formed due to peroxidation of lipids and detoxifies their effects [44].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…GSH can also protect brain from damage by peroxynitrite, hydroxyl free radicals, or reactive alkenals [63][64][65][66]75]. D609 may binds to reactive alkenals formed due to peroxidation of lipids and detoxifies their effects [44].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we showed that the xanthate D609, a glutathione mimetic [44], protects primary neuronal culture against Aβ (1-42)-induced oxidative stress and neurotoxicity in vitro [45] and against Aβ (1-42) in vivo [46]. D609 has the ability to scavenge hydrogen peroxide and hydroxyl free radicals [44].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations